Can he fix it? Yes, he can!. (8th December 2010) - Weston, Kelly; Bush, Kate; Afshar, Farid; Rowley, Steven
Abstract : We present a case in which a novel treatment was instigated by the patient to control symptoms of ocular neuromyotonia